Enhanced irradiation resistance of amorphous alloys by introducing amorphous/amorphous interfaces. (April 2019) - Huang, L.; Chen, Z.Q.; Liu, W.B.; Huang, P.; Meng, X.K.; Xu, K.W.; Wang, F.; Lu, T.J.
Abstract: To clarify the effect of amorphous/amorphous (A/A) interfaces during ion irradiation, the He ion irradiation responses of ZrCu/ZrCuNiAlSi A/A nanolaminates (A/ANLs) as well as ZrCu and ZrCuNiAlSi single-layered amorphous thin films were examined. The results showed the A/ANLs exhibited superior irradiation resistance compared with the corresponding single-layered thin films, as the former possessed better microstructure stability and higher He ion solubility than the latter during He ion irradiation. Besides, A/ANLs having more interfaces exhibited even better irradiation resistance than those having less. The enhanced irradiation resistance of A/ANLs was attributed to the sink effect of A/A interfaces, which effectively reduced the amount of radiation-induced "defects" and He bubbles. Highlights: The roles of amorphous/amorphous (A/A) interfaces during ion irradiation was studied. A/A nanolaminates (A/ANLs) had preferable irradiation resistance than the constituent single-layered amorphous thin films. A/ANLs having more interfaces exhibited even better irradiation resistance than those having less. The A/A interfaces might play a sink effect during ion irradiation.